"Defense by other means": future evolution(s) of cooperative threat reduction. Issue 5 (2nd September 2018) - Williams, Adam; Wilson, Rodney
ABSTRACT: This article discusses likely future contexts of, and options for, global threat-reduction activities to support nonproliferation goals over the next five to ten years. Threat-reduction activities span a continuum from unilateral actions that the United States might take with little cooperation and transparency at one end to cooperative actions associated with negotiated treaties and agreements at the other. This study focuses on cooperative approaches embodied in the Cooperative Threat Reduction (CTR) program, which has been the most visible program reducing the threats posed by weapons of mass destruction for over two decades. We argue that CTR's evolution can be described in terms of the relationship between the desired US influence on outcomes, the ability to generate a common threat definition, and appetite for collaboration on threat reduction. To that end, this article provides an introduction and overview of CTR initiatives over its twenty-seven-year history and a review of relevant legislation and trends. After introducing and describing the CTR Possible Futures Framework, this article offers five possible options for—and discusses the implications of—CTR's future evolution.